N‐Acetyl‐d‐galactosamine prevents soya bean agglutinin‐induced intestinal barrier dysfunction in intestinal porcine epithelial cells. Issue 4 (1st April 2019) - Zhao, Bao; Che, Dongsheng; Adams, Seidu; Guo, Nan; Han, Rui; Zhang, Chun; Qin, Guixin; Farouk, Mohammed Hamdy; Jiang, Hailong
Abstract: Soya bean agglutinin (SBA) is a glycoprotein and the main anti‐nutritional component in most soya bean feedstuffs. It is mainly a non‐fibre carbohydrate‐based protein and represents about 10% of soya bean‐based anti‐nutritional effects. In this study, we sought to determine the effects of N‐Acetyl‐D‐galactosamine (GalNAc or D‐GalNAc) on the damage induced by SBA on the membrane permeability and tight junction proteins of piglet intestinal epithelium (IPEC‐J2) cells. The IPEC‐J2 cells were pre‐cultured with 0, 0.125 × 10 −4, 0.25 × 10 −4, 0.5 × 10 −4, 1.0 × 10 −4 and 2.0 × 10 −4 mmol/L GalNAc at different time period (1, 2, 4 and 8 hr) before being exposed to 0.5 mg/ml SBA for 24 hr. The results indicate that pre‐incubation with GalNAc mitigates the mechanical barrier injury as reflected by a significant increase in trans‐epithelial electric resistance (TEER) value and a decrease in alkaline phosphatase (ALP) activity in cell culture medium pre‐treated with GalNAc before incubation with SBA as both indicate a reduction in cellular membrane permeability. In addition, mRNA levels of the tight junction proteins occludin and claudin‐3 were lower in the SBA‐treated groups without pre‐treatment with GalNAc. The mRNA expression of occludin was reduced by 17.3% and claudin‐3 by 42% ( p < 0.01). Moreover, the corresponding protein expression levels were lowered by 17.8% and 43.5% ( p < 0.05) respectively. However, in the GalNAc pre‐treated groups, occludin and claudin‐3 mRNAs were reduced by 1.6% ( p > 0.05) and 2.7% ( p < 0.01), respectively, while the corresponding proteins were reduced by 4.3% and 7.2% ( p < 0.05). In conclusion, GalNAc may prevent the effect of SBA on membrane permeability and tight junction proteins on IPEC‐J2s.